2021
DOI: 10.1158/2159-8290.cd-20-0896
|View full text |Cite
|
Sign up to set email alerts
|

A Chimeric GM-CSF/IL18 Receptor to Sustain CAR T-cell Function

Abstract: The inability of chimeric antigen receptor (CAR) T cells to sustain their effector function after repeated exposure to tumor cells is a major obstacle to their success in patients with solid tumors. To overcome this limitation, we designed a novel chimeric cytokine receptor to create an autocrine loop that links activation-dependent GM-CSF production by CAR T cells to IL18 receptor signaling (GM18). Expression of GM18 in CAR T cells enhanced their effector function in an antigen- and activation-dependent manne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 25 publications
4
31
0
Order By: Relevance
“…In repeat stimulation assays without IL-15, DNMT3A KO CAR T cells still had a proliferative advantage and produced more IL-10 in comparison to Ctrl KO CAR T cells; however, the effect was less pronounced. We and others have observed differential in vitro and in vivo requirements for exogenous cytokines of CAR T cells with second genetic modifications ( 47 , 60 ), highlighting differences between in vitro culture systems and preclinical in vivo models, which more closely mimic human tumors. Alloreactivity through endogenous TCRs is a concern when second genetic modifications are introduced into CAR T cells ( 61 ).…”
Section: Discussionmentioning
confidence: 86%
“…In repeat stimulation assays without IL-15, DNMT3A KO CAR T cells still had a proliferative advantage and produced more IL-10 in comparison to Ctrl KO CAR T cells; however, the effect was less pronounced. We and others have observed differential in vitro and in vivo requirements for exogenous cytokines of CAR T cells with second genetic modifications ( 47 , 60 ), highlighting differences between in vitro culture systems and preclinical in vivo models, which more closely mimic human tumors. Alloreactivity through endogenous TCRs is a concern when second genetic modifications are introduced into CAR T cells ( 61 ).…”
Section: Discussionmentioning
confidence: 86%
“…Our group recently showed the applicability of an "all-in-one" lentiviral vector system designed to engineer primary human T cells to target GD2 + GBM (15). In line with this, other recent studies took advantage of the strategy to co-deliver an additional cytokine and showed the potential of the armored CARs (14,55). Although the feasibility, efficacy, and selectivity to induce NFAT-driven cytokine secretion in a CARdependent fashion was successfully demonstrated (15), we encountered some challenges and problems when applying the system to NK cells.…”
Section: Discussionmentioning
confidence: 57%
“…A possible limitation of transgenic IL-18 expression is the recent discovery of an IL-18 binding protein (IL-18BP), an immune checkpoint, that inhibits IL-18 signaling; however, approaches to develop IL-18BP-resistant IL-18 are actively being explored ( 170 ). Lastly, a recent study has highlighted that it is feasible to design chimeric switch receptors that activate IL-18 signaling pathways in CAR T cells ( 171 ).…”
Section: Interleukin 1 Superfamily Of Cytokinesmentioning
confidence: 99%